Handedness predicts Social Preferences: Evidence connecting the Lab to the Field - Thomas Buser (Tinbergen Institute, 2010)
It is now generally accepted that some people are more altruistic, more trusting, or more reciprocal than others, but it is still unclear whether these differences are innate or a consequence of nurture. We analyse the correlation between handedness and social preferences in the lab and find that left-handed men are significantly more generous when recipients have the possibility to reciprocate and exhibit stronger positive reciprocity themselves. Left-handed women are significantly less altruistic. We test the external validity of these findings by connecting them to large-scale survey data from the Netherlands and the US covering altruistic behaviour and reciprocity outside the lab. The results largely carry over. We argue that our findings demonstrate that social preferences are at least partially determined by nature and help to shed light on their neural origins.
Keywords: D87; C91; 330; social preferences; handedness; external validity of lab experiments; Altruismus; Soziale Beziehungen; Niederlande; USA